Analisis Kompatibilitas Surfaktan Methyl Ester Sulfonate Berbasis Minyak Jelantah terhadap Brine Sintetik 20.000 ppm untuk Aplikasi Chemical EOR - Aristawidya Candraningtyas; Alim Aliami; Viola Sri Wahyuni; Devi Anggraini; Andi Atsiilah Besse Cambo; Muh Asraf (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Methyl Ester Sulfonate (MES) surfactant derived from used cooking oil has potential for Chemical Enhanced Oil Recovery (Chemical EOR), but its stability in brine must be evaluated before further application. This study aims to determine the compatibility of used cooking oil-based MES in synthetic brine with a salinity of 20,000 ppm. The experimental method was conducted by preparing MES solutions at concentrations of 0.3%, 0.7%, and 2%. Each solution was stirred at 60 °C for 1 minute and then heated at 60 °C for 3 hours. Visual observation was carried out based on solution clarity, suspension formation, and precipitation. The results showed that 0.3% MES was the most compatible condition because the solution remained clear and showed no visible precipitate. The 0.7% solution showed fine suspension, while the 2% solution appeared cloudy. Therefore, 0.3% MES is recommended for further testing.